Relationship between gambling motivation and internal- external locus of control - Kaya, Ferda Şule; Başkan, Ali (Journal of Dependence, 2020)
Objective: The aim of this study is to examine the relationship between the focus of internal and external control and gambling motivations.Method: The universe of the study consists of individuals between the ages of 18 and 55 who live and gamble in Istanbul. The participants of the study consisted of 121 individuals residing and gambling in Istanbul. In the study, demographic information form, gambling causes scale and internal-external control focus scale were used.Results: The gambling motivation and its sub-dimensions fun / excitement, monetary, socialization and avoidance motivations were statistically significantly different based on the locus of control. In addition, according to the results of the regression analysis, the control focus significantly predicted gamble motivation (R2 = 0.327) and sub-dimensions which are fun / excitement (R2 = 0.305), monetary (R2 = 0.205), socialization (R² = 0.090) and avoidance (R² = 0.154) motivations.Conclusion: The relationship between locus of control and gambling motivation showed that the locus of control is an important factor. In addition, it was understood that the start of gambling behavior and continuation gambling behavior affected from different motivations than each other.
Keywords: Gambling; pathological gambling; iıncentives; internal-external control